Modes of application of cobalt, molybdenum and Azospirillum brasilense on soybean yield and profitability - Galindo, Fernando S. [UNESP]; Teixeira Filho, Marcelo C. M. [UNESP]; Buzetti, Salatier [UNESP]; Santini, Jose M. K. [UNESP]; Ludkiewicz, Mariana G. Z. [UNESP]; Baggio, Guilherme [UNESP] (Univ Federal Campina Grande, 2017)
The use of cobalt (Co) and molybdenum (Mo) along with the co-inoculation with Azospirillum brasilense on soybean can contribute to biological nitrogen fixation (BNF), allowing higher yields. Thus, this work aimed to study the technical and economic viability of soybean in the Cerrado, according to the mode of application of Co + Mo, and seed or leaf co-inoculation with Azospirillum brasilense. The experiment was conducted in Selviria-MS, in a no-tillage system in an Oxisol, arranged in a randomized block design with six treatments (seed application of two treatments with Co + Mo, with or without inoculation with A. brasilense, respectively; Foliar application of Co + Mo at soybean V3 stage; Foliar application of Co + Mo together with A. brasilense at V3 growth stage; Foliar application of A. brasilense at V3 growth stage; and the Control, consisting of only inoculation with Rhizobium), and four replicates. Seed application of Co + Mo associated with seed inoculation with A. brasilense promoted the highest leaf N content, hundred-grain weight, yield and profitability with the soybean crop.
Keywords: co-inoculation with Azospirillum brasilense; total operating cost; economic viability; technical viability; leaf nitrogen content